Broadband high gain cavity resonator antenna using planar electromagnetic bandgap (EBG) superstrate - Dey, Soumik; Dey, Sukomal (International journal of microwave and wireless technologies, 2023)
This paper presents a broadband miniaturized Fabry–Perot cavity resonator antenna (CRA) made of novel electromagnetic bandgap (EBG) superstrate as partially reflecting surface (PRS) and reactive impedance surface (RIS) backed rectangular patch antenna. To the best of the authors' knowledge, the proposed EBG exhibits the highest stopband bandwidth (BW) with a bandgap existing between 7.37 and 12.4 GHz (50.9%). Frequency-selective property of the EBG is utilized under plane wave incidence to demonstrate it as PRS superstrate in CRA antenna. The cavity is excited with a rectangular microstrip antenna which is made of two dielectric substrates with an additional RIS layer sandwiched between them. The RIS provides wideband impedance matching of the primary feed antenna. A 7 × 7 array of the EBG superstrate is loaded over the patch antenna having an overall lateral dimension of only 45 × 45 mm2 or 1.62 λ0 × 1.62 λ0 where λ0 is the free space wavelength at the center frequency of 10.8 GHz. The proposed Fabry–Perot CRA (FP-CRA) achieves gain enhancement of 6.59 dB as compared with the reference antenna and has a 10 dB return loss BW of 23.79% from 10.07 to 12.79 GHz. A prototype of the FP-CRA is fabricated and experimentally tested with single and dual layers of EBG superstrate. Measured results show BWs of 21.5 and 24.8% for the two cases with peak realized gain of 12.05 and 14.3 dBi, respectively. Later a four-element antenna array with corporate feeding is designed as the primary feed of the CRA. The simulation result shows a flat gain of >13 dBi with gain variation <1.2 dB over the impedance BW of 13.2%.